Charge distribution in nano‐scale grains of magnesium aluminate spinel. Issue 2 (31st October 2016) - Halabi, Mahdi; Ezersky, Vladimir; Kohn, Amit; Hayun, Shmuel
Abstract: Charge distribution in magnesium aluminate spinel (MAS) results in the formation of a space‐charge region that plays a critical role in assigning functional properties. Significant theoretical advances explaining this phenomenon have been accomplished, even though quantitative experimental support from nano‐scale granular MAS is only indirect. In this work, the electrostatic potential distribution in nano‐scale grains of nonstoichiometric MAS (MgO·0.95Al2 O3 and MgO·1.07Al2 O3 ) was measured by off‐axis electron holography (OAEH) and compared to the distribution of cations and defects in this material as measured by electron energy‐loss spectroscopy (EELS). In this manner, we studied the roles of composition, grain size, and applied electric field (EF) on the formation of a space‐charge region. We quantitatively demonstrated that regardless of grain size, the vicinity of MgO·0.95Al2 O3 grain boundaries presented an excess of Mg +2 cations, whereas the vicinity of MgO·1.07Al2 O3 grain boundaries included an excess of Al +3 cations. The degree of structural disorder (ie, the inversion parameter, i ) indicated that as‐synthesized MAS were significantly disordered ( i between 0.37 and 0.41), with values decreasing toward equilibrium ordering values following annealing ( i between 0.27 and 0.31). The application of an external 150 V/cm EF during annealing further enhanced lattice ordering ( i between 0.16 and 0.19). Such variations in the distribution of cations and defects should determine the space‐charged potential (SCP). However, using these measurements to calculate the SCP was not possible due to the wide range of values reported for formation energies of defects (0.82‐8.78 eV). Consequently, we correlated local ionic ordering with electrostatic potential in nonstoichiometric MAS. The magnitudes of the SCP in both MgO·0.95Al2 O3 and MgO·1.07Al2 O3 decreased following annealing from −3.4 ± 0.3 V and 2.0 ± 0.2 V to −2.0 ± 0.2 V and 1.6 ± 0.1 V, respectively.